Translation and cross-cultural adaptation of the Brazilian version of the Reading Anxiety Scale: Short version - PICCOLO, Luciane da Rosa; GIACOMONI2, Claudia Hofheinz; LIMA, Melina; BASSO, Fabiane Puntel; HAASE, Vitor Geraldi; ZBORNIK, John; SALLES, Jerusa Fumagalli de (Estudos de Psicologia (Campinas), 2023)
ERRATA